Repertoires, identities, and issues of collective action in the candlelight movement of South Korea. (December 2020) - Chae, Young-Gil; Cho, Jaehee; Cho, Inho
In this case study, we examine the evolution of particular themes and identities of collective action. Using the 2016 Candlelight Movement in South Korea as a case study, we attempt to understand how communication processes construct the sociocultural meanings of collective action. We argue that understanding a social movement requires comprehension of the communicative actions of the movement participants, either physically or symbolically engaged, through which they together make sense of the broad contexts and meanings of the movement as they actively pursue construction of the identities and themes of the collective action. Based on a communication perspective of social movements, we developed three research questions regarding the specific features of the collective action repertoire, collective identities and issue framing. Considering the extensive impact of media communication technologies in mobilising collective action in South Korea, especially mobile social networking platforms, we chose one of the most popular social network sites, Twitter, as the data source of communicative actions for the study. Content analysis and semantic network analysis was conducted with a sample of 1, 779, 902 tweets. Based on the analyses, we suggest that the collective action and identities both shape and are shaped by the communication networks of the movement participants as they interact with not only the counter-movement actors, but also the movement's social, economic and cultural conditions.